2010
DOI: 10.1111/j.1365-2044.2010.06247.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic guided axillary plexus blocks with low volumes of local anaesthetics: a crossover volunteer study

Abstract: SummaryOur study group recently evaluated an ED 95 local anaesthetic volume of 0.11 ml.mm )2 crosssectional nerve area for the ulnar nerve. This prospective, randomised, double-blind crossover study investigated whether this volume is sufficient for brachial plexus blocks at the axillary level. Ten volunteers received an ultrasonographic guided axillary brachial plexus block either with 0.11 ('low' volume) or 0.4 ('high' volume) ml.mm )2 cross-sectional nerve area with mepivacaine 1%. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 30 publications
1
30
0
Order By: Relevance
“…Several volume reduction studies have shown the highly effective application of ultrasound for ulnar [18], sciatic [19] and ilioinguinal-iliohypogastric blocks [20] in adults and children. In addition, Ó Donnell et al and Marhofer et al [21,22] have described low volume blockade of the axillary part of the brachial plexus. Co-incidental blockage of the great auricular nerve can occur if large volumes of local anaesthetic are injected but that cannot have been the case in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Several volume reduction studies have shown the highly effective application of ultrasound for ulnar [18], sciatic [19] and ilioinguinal-iliohypogastric blocks [20] in adults and children. In addition, Ó Donnell et al and Marhofer et al [21,22] have described low volume blockade of the axillary part of the brachial plexus. Co-incidental blockage of the great auricular nerve can occur if large volumes of local anaesthetic are injected but that cannot have been the case in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Ponrouch [12] also indicated a positive correlation between the administered volume of the anaesthetic and the time of duration for the median nerve and the ulnar nerve block. Marhofer [14] noticed the trend towards prolongation of analgesia time after administration with a higher volume of local anaesthetic agent. This finding is not unambiguous, regardless of whether this effect may be caused by an increase in volume or the dose of local anaesthetic agent.…”
Section: Time Of Block and Onset And Duration Of Analgesiamentioning
confidence: 99%
“…With the ultrasound to guide peripheral nerve block, the total volume of local anesthetic can be dramatically reduced so as to limit the risk of toxic side effects due to the drug. [3][4][5][6] The aim of this study is to determine the effectiveness of these two techniques, so that a more effective technique can be used for anesthesia superior extremity orthopedic surgery or can be used as an alternative option, and the authors believe that the particular regional anesthesia regional anesthesia is to minimize the inflammatory process that occurs as a result of actions surgery.…”
Section: Introductionmentioning
confidence: 99%